Colonizing Christianity: Greek and Latin religious identity in the era of the Fourth Crusade - Demacopoulos, George E. (Orthodox Christianity and contemporary thought, 2019)
Inhaltsverzeichnis: Introduction -- Robert de Clari -- Gunther of Pairis's Hystoria Constantinopolitana -- Innocent's ambivalence -- Demetrios Chomatianos : colonial resistance and the fear of sacramental miscegenation -- George Akropolites and the counterexample(s) -- The Chronicle of Morea -- Conclusion.